The integration of rainwater harvesting facility into the house of Poblacion, Candijay, Bohol based on Type IV Philippine Climate Classification - Pascual, Myson Lloyd H.; Nicolo C. del Castillo (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Water scarcity is a significant concern worldwide. Despite falling under type IV climate
classification, where rainfall is relatively evenly distributed throughout the year, Bohol
still faces water scarcity in certain areas. One such area is Poblacion, Candijay, Bohol,
where water shortages are most severe from March to May. The community's water
supply primarily relies on wells and mountain springs. Although residents have
implemented rainwater collection using pails, barrels and drums, this system remains
inadequate and insufficient to meet their non-potable water demands. To address this
issue, the study aims to explore how to integrate rainwater harvesting into the initial
house designs. It examines 40 houses in Poblacion as a reference for building
technology styles and practices, as well as water demand within the community. The
study utilized recent precipitation data from PAGASA along with water consumption
data obtained from surveys to determine the minimum roof size and tank capacity.
Furthermore, systematic observations and considerations of building technology and
materials were considered in the design transformation process. The study found that
the roof area is directly proportional to the amount of water collected and inversely
proportional to the level of precipitation. The findings indicate that roof area
significantly affects water collection, and the design must consider the month with the
least rainfall to ensure adequacy. Tank dimensions should correspond to monthly
consumption and average excess rainwater to maximize collection. In developing the
models, the study uses factors derived from the survey questions answered by the
largest number of participants. These factors include user profiles, monthly water
consumption, and the predominant architectural styles of houses within the community.
These models show that rainwater harvesting can be effectively incorporated into the
initial design of residential buildings with careful consideration of the aforementioned
factors. The study promotes sustainability by incorporating rainwater harvesting
facilities, making it a vital component of contemporary building practices that
transform residential designs into more relevant and climate-responsive architecture.
Include appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Water harvesting -- Candijay (Bohol); Architecture, Domestic -- Design